The experimental study of the effective thermal conductivity of bundles of rectangular steel sections = Badania eksperymentalne efektywnej przewodności cieplnej wiązek stalowych profili prostokątnych - Wyczółkowski, Rafał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Bundles of rectangular steel sections are examples of the porous charge. Due to the voids within the sections, this type of charge is characterized by porosity even exceeding 85%. This makes the thermal properties of these elements, expressed by the effective thermal conductivity kef, totally different from the thermal conductivity of steel.
Keywords: przewodnictwo cieplne; profile stalowe; obróbka cieplna; urządzenia grzejne; effective thermal conductivity; steel sections bundles; heat treatment; hot plate apparatus